The implementation of a pathway and care bundle for the management of acute occlusive arterial mesenteric ischemia reduced mortality. Issue 3 (September 2021) - Tolonen, Matti; Lemma, Aurora; Vikatmaa, Pirkka; Peltola, Erno; Mentula, Panu; Björkman, Patrick; Leppäniemi, Ari; Sallinen, Ville
Abstract : BACKGROUND: Acute mesenteric ischemia (AMI) is a disease with high mortality and requires a multidisciplinary approach for effective management. A pathway and care bundle were developed and implemented with the objective to reduce mortality. The aim of this retrospective comparative study was to analyze the effects of the pathway on patient management and outcome. METHODS: All consecutive patients operated in a secondary and tertiary referral center because of occlusive arterial AMI were identified between 2014 and April 2020. The pathway aimed to increase overall awareness, and hasten and improve diagnostics and management. Patients treated before implementation of the pathway (pregroup, years 2014–2017) were compared with patients treated using the pathway (postgroup, May 2018 to April 2020). Univariate and multivariate analyses were used to compare the groups. RESULTS: There were 78 patients in the pregroup and 67 patients in the postgroup with comparable baseline characteristics and disease acuity. The postgroup was more often diagnosed with contrast-enhanced computed tomography (58 [74%] vs. 63 [94%], p = 0.001) and had shorter mean in-hospital delay to operating room (7 hours [interquartile range, 3.5–12.5] vs. 3 hours [interquartile range, 2–11], p = 0.023). Revascularization was done more often in the postgroup (53 [68%] vs. 56 [84%], p = 0.030) especially using endovascular treatment (26 [33%] vs. 43 [64%], p < 0.001). Thirty-day mortality was lower in the postgroup (23 [51%] vs. 17 [25%], p = 0.001). Being managed in the postgroup remained as a protective factor (odds ratio, 0.32; 95% confidence interval, 0.14–0.75; p = 0.008) for 30-day mortality in the multivariate analysis. CONCLUSION: Implementing a pathway and care bundle resulted in enhanced regional and in-hospital awareness of AMI, more appropriate computed tomography imaging, shorter in-hospital delays, increased number of revascularizations, and, hence, lower mortality. LEVEL OF EVIDENCE: Therapeutic/Care Management, level IV. Abstract : Supplemental digital content is available in the text.